3D implant of copolyamide associated with thermoplastic elastomer (PCTPE) for tracheal repair in rabbits (Oryctolagus cuniculus): preliminary study - Rein, Ariadne [UNESP]; da Costa, Marcelo Carrijo [UNESP]; Montanhin, Gabriel [UNESP]; Fernandes, Gustavo [UNESP]; Leite, Marcella Dall Agnol [UNESP]; Carra, Gabriel João Unger [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP]; Dias, Luís Gustavo Gosuen Gonçalves [UNESP]; de Sá Rocha, Thiago André Salvitti; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2024)
Large segmental tracheal defects can pose a serious clinical challenge owing to the lack of suitable substitutes for reconstructive surgery. Polymeric biomaterials are widely used in medicine. However, the implantation of biomaterials triggers a series of biological events, and material biocompatibility is of paramount importance in regenerative medicine. The objective of this study was to evaluate the use of a copolyamide associated with thermoplastic elastomer (PCTPE) in 3D-printed prostheses for repairing partial tracheal defects in rabbits. Sixteen male New Zealand White rabbits were used, and partial tracheal defects were created in the ventral region from the 4th to the 8th tracheal ring. The animals were subdivided into groups (n=4) based on the time of euthanasia, scheduled at seven days (G7), 15 days (G15), 30 days (G30), and 60 days (G60). Histopathological analysis with hematoxylin and eosin staining revealed that the 3D implant of PCTPE exhibited a foreign body reaction, and inflammation persisted for up to 60 days. Histochemistry with picrosirius red revealed a tendency for a greater amount of type I collagen to accumulate in the early stages of inflammation, whereas type III collagen was predominant in later evaluation periods. These findings suggest an exacerbated and inadequate tissue-material interface reaction and perpetuation of the inflammatory process.
Implante 3D de copoliamida associada à elastômero termoplástico (PCTPE) para reparação traqueal de coelhos (Oryctolagus cuniculus): estudo preliminar
Keywords: bioprosthesis; picrosirius; polymers; regeneration; tracheoscopy